Application of The Asoka Model With Street Photography Media Based on Local Wisdom in Improving Students’ Creative Thinking Abilities - Sofino, Sofino; Gusti, Ririn; Hutauruk, Lenni Mantili; Pradikto, Bayu (JIV-Jurnal Ilmiah Visi, 2024)
The results of the monitoring of the Non-formal Education Study Program coordinator for the student creative work course (PNF-202) semester III in the 2023-2024 academic year are practical courses that have minimal field practice. This course allows students to engage in activities in the community and see portraits of social and educational issues in the community. The results of SIEPEL v2.0 University of Bengkulu in 2023-2024 stated that this course had the lowest average satisfaction in semester III, especially in terms of pedagogical and social competence. Even 65% of students want to improve their learning, especially in practical activities in the community, using accurate models, methods, and approaches. This study aimed to analyze the application of the ASOKA model with street photography media based on local wisdom in improving students’ creative thinking skills. This study uses a non-equivalent control group design experimental method with a sample of 26 students in semester III-A and 25 students in semester III-B as the control class. Data analysis was done using SPSS 22 software on pretest and posttest data, normality test, homogeneity test, and t-test. The study results indicate that applying the ASOKA model with street photography media based on local wisdom improves students’ creative thinking skills in fluency, flexibility, originality, and elaboration. The t-test or hypothesis test results show that t-count = 10.983> t-table = 2.010, which means that the model used significantly improves students’ creative thinking skills more than conventionall.